PENYULUHAN TUBERKULOSIS PARU KEPADA MASYARAKAT LINGKUNGAN HAMPARAN PERAK KECAMATAN DELI SERDANG - Situmeang, Ivonne Ruth Vitamaya Oishi; Simanjuntak, Maestro B. U.; L. Tobing, Paul S. M.; Sinurat, Suryati; Harefa, Alowadodo; Simanullang, Okkasa Obadiah (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
The aim of community service activities is to implement community service in implementing the Tri Dharma of higher education as well as contributing ideas and transferring knowledge to mothers, fathers, children and youth. This service activity was carried out on March 24 2022, with the material Lung Tuberculosis. This topic is really needed in order to provide information and knowledge about Pulmonary Tuberculosis, starting from how to prevent and treat Pulmonary TB patients. This topic was deliberately chosen considering that currently TB is still the biggest health problem in the world, apart from that, our country, Indonesia, has the second highest rate of TB. Therefore, the role of medical personnel is very important in providing education to the public to behave in a clean manner at home and around the home environment, where this activity aims to reduce the risk of transmission and infection of Pulmonary Tuberculosis.